Humor Effectiveness in L2 Classrooms: The Case of Rural School EFL Students - Mudra, Heri (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
This study aimed to measure types, levels, and perceptions towards the application of humor as a supporting material in EFL classrooms. One hundred and thirteen rural school EFL students were involved as the participants of this mixed-methods study. As for quantitative results, humor was revealed to have positive influence on EFL students’ learning development by facilitating the lesson and encouraging learning enthusiasm. Although some aspects of L2 humor were not believed to be helpful, other aspects such as modelling English use and usage and authentic materials proved that such L2 humor was advantageous. Meanwhile, interview results showed that L2 humor was considered paramount that it helped to progress English learning, improve learning strategies, and increase motivation. The combination between both results prove that L2 humor is not only entertaining, but also prospective for those who expect a more realistic or knowledgeable material that does not cause stress or anxiety in learning English, particularly in a rural context. In addition, this study was limited on quantitative and qualitative perceptions, but it did not attempt to implement L2 humor through an action research.